JENIS-JENIS SKALA SIKAP: PENGUKURAN OPINI DAN PERSEPSI - Adi Sulistyo Wibowo; Ahmad Fathir Qodri; Achmad Rasyid Ridha (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Measuring attitudes, opinions, and perceptions is an important component in social sciences, psychology, and education. This article discusses various types of attitude scales used in quantitative research, such as the Likert Scale, Guttman, Thurstone, and Semantic Differential. Each scale is analyzed based on its advantages, disadvantages, and the context of its application. This study uses a literature study approach and aims to help researchers choose a scale that suits their research objectives. The results of the discussion show that the choice of scale greatly affects the validity and reliability of the data obtained. This study also provides practical guidance in choosing the right scale for various types of social studies.